AB0646 Predicting Temporal Artery Biopsy Results… Offering Insights Into Temporal Arteritis Diagnosis. (9th June 2015) - Jutley, G.S.; Ahluwalia, A.S.; Ali, T.
Abstract : Background: Biopsy of the temporal artery is considered fundamental to making the diagnosis of temporal arteritis. Besides carrying a significant false negative rate owing to skip lesions, the procedure has a small risk of significant complications including facial nerve injury 1, scalp necrosis 2 and stroke 3 . The procedure may be contraindicated by delay in undertaking the biopsy from commencement of treatment, patient's wishes or bleeding diathesis. Objectives: To study the incidence of biopsy-proven temporal arteritis in the population surrounding Chesterfield Royal Hospital, United Kingdom. Methods: A retrospective review of 235 consecutive patients who underwent a temporal artery biopsy in Chesterfield Royal Hospital from January 2009 to January 2015. Study variables included age at diagnosis, gender, CRP, ESR and ALP results prior to treatment. Results: Among these 235 patients who underwent temporal artery biopsy, the mean age of those in the biopsy-positive group, 76.4 years (95% CI 73.8, 79.0), was higher than that of those in the biopsy-negative group, 70.4 (95% CI 69.0, 71.8). Using a two sample t-test, this generated a p value of 0.0002. A logistic regression model showed there is a statistically significant increase in the odds of a positive temporal artery biopsy of 1.072487 (CI 1.03045 to 1.116238) for every year increase of age, in addition to an odds increase of 1.022069 (CI 1.011327 to 1.032925) for every 1mm/hr increase in ESR. There was no statistical correlation between biopsy positive and biopsy-negative groups for CRP or ALP level; but a number patients had no CRP (97) or ALP (71) measured prior to diagnosis. Conclusions: Our results show there is a significant increase of likelihood of a positive temporal artery biopsy as the patient's age increases and the higher the value of ESR. Given a large enough sample, these results suggest that a scoring system may be created which can attempt to predict the likelihood of a positive temporal artery biopsy. This may be useful for patients in which temporal arteritis is suspected and biopsy is precluded. References: Slavin ML. Brow droop after superficial temporal artery biopsy. Arch Ophthalmol 1986. 1041127. Dummer W, Zillikens D, Schulz A. et al. Scalp necrosis in temporal (giant cell) arteritis:implications for the dermatologic surgeon. Clin Exp Dermatol 1996. 21154–158.158. Haist SA. Stroke after temporal artery biopsy. Mayo Clin Proc 1985. 6053. Disclosure of Interest: None declared